M2 macrophage polarization: a potential target in pain relief - Zhao, Wenjing; Ma, Lulin; Deng, Daling; Zhang, Tianhao; Han, Linlin; Xu, Feng; Huang, Shiqian; Ding, Yuanyuan; Chen, Xiangdong (Frontiers in Immunology, 2023)
Pain imposes a significant burden on patients, affecting them physically, psychologically, and economically. Despite numerous studies on the pathogenesis of pain, its clinical management remains suboptimal, leading to the under-treatment of many pain patients. Recently, research on the role of macrophages in pain processes has been increasing, offering potential for novel therapeutic approaches. Macrophages, being indispensable immune cells in the innate immune system, exhibit remarkable diversity and plasticity. However, the majority of research has primarily focused on the contributions of M1 macrophages in promoting pain. During the late stage of tissue damage or inflammatory invasion, M1 macrophages typically transition into M2 macrophages. In recent years, growing evidence has highlighted the role of M2 macrophages in pain relief. In this review, we summarize the mechanisms involved in M2 macrophage polarization and discuss their emerging roles in pain relief. Notably, M2 macrophages appear to be key players in multiple endogenous pathways that promote pain relief. We further analyze potential pathways through which M2 macrophages may alleviate pain.